Bethabara Moravian Church in the snow, with the stockade at left. - (:unkn) unknown (Forsyth County Public Library, 2009)
Photo made in the 1950s.
Bethabara Moravian Church in the snow, with the stockade at left.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth